1993
DOI: 10.1136/vr.132.17.436
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound to diagnose testicular degeneration in a goat

Abstract: A seven-year-old infertile British alpine buck with small testes had bilateral testicular degeneration, as confirmed by the presence of a large number of dead and abnormal spermatozoa and a low percentage of progressively motile spermatozoa in its semen. Histopathological examination of the testes post mortem showed typical degenerative changes in the seminiferous tubules, with some tubules showing evidence of calcification. Ultrasonographically, the testicular parenchyma was uncharacteristically heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…The mediastinal line showed reduced heterogeneous echogenicity, likely increase the parenchyma showed heterogeneous echogenicity and a small amount of free fluid in the pouch. Ahmad et al (1993 ) and Ahmad and Noakes (1995 ) observed similar hyperechoic areas in the testicular parenchyma of infertile male goats and being diagnosed as testicular degeneration showing a similar feature as in the present study. Ali et al (2011) studied ten cases of infertility in buffalo bulls through ultrasound, and observed six cases of change in ultrasound images, with three cases diagnosed as testicular degeneration.…”
Section: Testicular Degenerationsupporting
confidence: 89%
“…The mediastinal line showed reduced heterogeneous echogenicity, likely increase the parenchyma showed heterogeneous echogenicity and a small amount of free fluid in the pouch. Ahmad et al (1993 ) and Ahmad and Noakes (1995 ) observed similar hyperechoic areas in the testicular parenchyma of infertile male goats and being diagnosed as testicular degeneration showing a similar feature as in the present study. Ali et al (2011) studied ten cases of infertility in buffalo bulls through ultrasound, and observed six cases of change in ultrasound images, with three cases diagnosed as testicular degeneration.…”
Section: Testicular Degenerationsupporting
confidence: 89%
“…Despite an extensive literature search, only a few papers on testicular calcifications in ruminants could be found. For example, testicular calcifications were found in association with testicular dysgenesis in Sitka Black-tailed deer in Alaska , testicular degeneration in beef bulls having small testes (Veeramachaneni et al, 1986), degenerative changes in the seminiferous tubules of goats occurring spontaneously (Ahmad et al, 1993) or with experimentally induced Trypanosoma evansi orchitis (Ngeranwa et al, 1991). In Merino sheep the prevalence of testicular lesions, including calcifications, increased with age (Watt, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…These hyperechoic areas were assumed to represent mineralization in the testes. Ahmad et al [33] and Ahmad and Noakes [5] observed hyperechoic areas in the testicular parenchyma of infertile bucks. According to Lenz and Giwercman [34], such bright echogenic spots were representing microlithiasis or microcalcifications.…”
Section: Discussionmentioning
confidence: 99%